2006
DOI: 10.1128/iai.00469-06
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Disease Remission in the Mouse Model of Lyme Borreliosis

Abstract: In the mouse model of Lyme borreliosis, the host immune response during infection with Borrelia burgdorferi results in the remission of carditis and arthritis, as well as global reduction of spirochete numbers in tissues, without elimination of infection (28). These events were recapitulated by passive transfer of immune serum from infected immunocompetent mice or T-cell-deficient mice to severe combined immunodeficient (SCID) mice. Previous studies have shown that immune serum is reactive against arthritis-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
89
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 47 publications
5
89
0
1
Order By: Relevance
“…IgG responses to DbpA appeared T independent, while BmpA-IgG responses were somewhat increased in CD4 T-deficient mice. Consistent with these data, a previous study with T cell-deficient TCR␤/␦ Ϫ/Ϫ mice also found a lack of T dependence of the DbpA response (20). Furthermore, repeated immunization with recombinant DbpA from cN40 failed to induce measurable CD4 T cell responses (data not shown).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…IgG responses to DbpA appeared T independent, while BmpA-IgG responses were somewhat increased in CD4 T-deficient mice. Consistent with these data, a previous study with T cell-deficient TCR␤/␦ Ϫ/Ϫ mice also found a lack of T dependence of the DbpA response (20). Furthermore, repeated immunization with recombinant DbpA from cN40 failed to induce measurable CD4 T cell responses (data not shown).…”
Section: Resultssupporting
confidence: 86%
“…DbpA-specific T cell-independent antibodies served as a control (Fig. 1C) (8,20). We utilized a method for detecting changes in the overall avidity of B. burgdorferi antigen-specific serum antibodies over time by comparing antibody binding after high-and low-stringency washes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of spirochetes to embed themselves in dense collagen bundles may offer protection from both antibodies and antibiotics. [52][53][54][55] Putting all this information together, we can speculate that CD14 not only helps in the activation of MMP-9 necessary for degradation of existing collagen but also may limit the continued production of collagen. Control of these fibrotic processes by CD14 not only leads to higher neutrophil recruitment and clearance of spirochetes but also deprives B. burgdorferi of "hide-outs" within joints.…”
Section: Discussionmentioning
confidence: 98%